Implementation of Innovative Technologies During the Modernization of Existing Level Crossings for High-Speed Train Traffic - Kurhan, M. B.; Luzhytskyi, O. F.; Ivanov, R. V.; Khmelevska, N. P.; Khmelevskyi, V. S. (Science and Transport Progress, 2024)
Implementation of Innovative Technologies During The Modernization of Existing Level Crossings for High-Speed Train Traffic Purpose. The main purpose of the study is to review innovative technologies for improving safety at the intersection of railways and roads. The object of research is the processes of functioning – railway crossings with different intensity and parameters of traffic, which require solving a fairly wide range of theoretical, practical and organizational tasks. Methodology. The study is based on the theory of mathematical modeling and numerical methods of computer calculations. The subject of the study is indicators that allow to assess the state of safety after modernization or new design solutions. Findings. A model of an improved method of the final coefficient is proposed, which allows predicting changes in the initial data and obtaining different values of the final coefficient, and thus planning measures to introduce innovative technologies that improve traffic safety at level crossings. Closing railroad crossings or switching to a two-level intersection of railroad and road (overpasses) is the only way to completely eliminate the risk. However, it is virtually impossible to close all railroad crossings immediately. In addition to financial and practical constraints, user convenience should still be a key factor. Using hierarchy, brainstorming, and other methods, a reliable set of indicators can be identified to assess and ensure the overall safety of passengers and vehicles related to all aspects of the design, construction, maintenance, and operation of the rail network. The introduction of innovative technologies during the modernization of existing level crossings is an important step towards organizing high-speed train traffic. These technologies will increase the level of traffic safety at railroad crossings and protect people's lives. Originality. The scientific and applied problem of introducing innovative technologies during the modernization of existing level crossings for the organization of high-speed train traffic has been solved. Practical value. The implementation of a sound technology for the modernization of existing level crossings will provide a significant increase in traffic safety and throughput.